Molecular Crosstalk between Integrins and Cadherins: Do Reactive Oxygen Species Set the Talk?. (13th December 2011) - Goitre, Luca; Pergolizzi, Barbara; Ferro, Elisa; Trabalzini, Lorenza; Retta, Saverio Francesco
Abstract : The coordinate modulation of the cellular functions of cadherins and integrins plays an essential role in fundamental physiological and pathological processes, including morphogenesis, tissue differentiation and renewal, wound healing, immune surveillance, inflammatory response, tumor progression, and metastasis. However, the molecular mechanisms underlying the fine-tuned functional communication between cadherins and integrins are still elusive. This paper focuses on recent findings towards the involvement of reactive oxygen species (ROS) in the regulation of cell adhesion and signal transduction functions of integrins and cadherins, pointing to ROS as emerging strong candidates for modulating the molecular crosstalk between cell-matrix and cell-cell adhesion receptors.